2012
DOI: 10.3109/17435390.2012.710660
|View full text |Cite
|
Sign up to set email alerts
|

Serum kinetics, distribution and excretion of silver in rabbits following 28 days after a single intravenous injection of silver nanoparticles

Abstract: Serum kinetics, tissue distribution, and excretion of citrate-coated silver nanoparticles (AgNPs) were investigated in rabbits (n = 4) up to 28 days after a single intravenous injection. Following a single injection of AgNPs, the AUC(last) was reported to be 3.65 ± 0.68 μg·day/ml in 5 mg/kg-treated group and 0.90 ± 0.16 μg·day/ml in 0.5 mg/kg-treated group, respectively. The accumulation of silver was observed in all the tested organs including liver, kidney, spleen, lung, brain, testis, and thymus at 1 day, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 30 publications
11
53
0
2
Order By: Relevance
“…Selected studies on biodistribution of AgNPs in mammalian brain are listed in Table II. Lee and co-workers observed that after a single intravenous injection of citrate-coated AgNPs (7.9 nm), they become distributed in serum, liver, kidney, spleen, lungs, brain, testes and thymus of rabbits. Significantly, the presence of silver nanoparticles was observed at time points 1, 7 and 28 days after the injection [73]. Silver was also detected in brain of rats at 24, 96 and 168 h after an intraperitoneal injection of bovine serum albumin-coated 2 nm AgNPs [45].…”
Section: Routes Of Exposure and Biodistribution Of Agnps In Mammalianmentioning
confidence: 89%
See 2 more Smart Citations
“…Selected studies on biodistribution of AgNPs in mammalian brain are listed in Table II. Lee and co-workers observed that after a single intravenous injection of citrate-coated AgNPs (7.9 nm), they become distributed in serum, liver, kidney, spleen, lungs, brain, testes and thymus of rabbits. Significantly, the presence of silver nanoparticles was observed at time points 1, 7 and 28 days after the injection [73]. Silver was also detected in brain of rats at 24, 96 and 168 h after an intraperitoneal injection of bovine serum albumin-coated 2 nm AgNPs [45].…”
Section: Routes Of Exposure and Biodistribution Of Agnps In Mammalianmentioning
confidence: 89%
“…Park and co-workers observed that the bioavailability of AgNPs (7.9 nm) after oral administration to rats was very low, in the range of 1.2% to 4.2% based on a single dose [101]. Following entry into the systemic circulation, AgNPs can become distributed among a number of mammalian organs, most notably liver and spleen [73,145]. Furthermore, silver nanoparticles have been found in blood, lungs, kidney, brain, heart and genital organs [67,70,73,81,101,131,145].…”
Section: Routes Of Exposure and Biodistribution Of Agnps In Mammalianmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that Ag NPs injected in rats can be translocated from the blood to all the main organs and that the concentration of Ag in tissues was significantly higher in rats treated with 20 nm Ag NPs when compared with 200 nm Ag NPs [100]. The accumulation of Ag was also observed in all examined rabbit organs, including liver, kidney, spleen, lung, brain, testis and thymus up to 28 days following a single intravenous dose [155]. An uptake of Ag NPs into mammalian cells such as lung epithelial cells could be shown in vitro by TEM using an airliquid exposure cell system to avoid particle dissolution (and aggregation) in cell culture media.…”
Section: Uptake Of Ag Nanoparticles In Mammalsmentioning
confidence: 98%
“…12,13 AgNPs were found in various body tissues, including the blood, brain, liver, spleen, kidneys, thymus, lungs, and heart. [14][15][16][17][18][19] Previous studies have demonstrated that AgNPs can exert cytotoxic and genotoxic effects both in vitro (human cell lines [20][21][22][23][24][25] ) and in vivo (mice 26,17 and fish 27,28 ). Oxidative stress can strongly affect testicular functions important for spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%